Pole and Line Fishery Sustainability Status Based on Business Feasibility At the Bacan Coastal Fishing Port, South Halmahera Regency - Adi Noman Susanto (Sangia Publishing, 2021)
The waters of Bacan Island are a fishing ground for skipjack tuna (Katsuwonus pelamis), using pole and line fishing gear with FADs. The pole and line fishery business carried out by fishermen or entrepreneurs at the Bacan coastal fishing port should earn a continuous profit. Therefore, a business feasibility study on the pole and line fishery business is very important given the considerable uncertainty in the business, because this fishery business is highly dependent on the fishing season and natural factors. The research has been carried out in the coastal fishing port of Bacan. Data collection in the field was carried out for 2 weeks, from 6 to 19 May 2021. The study used a descriptive survey method. Data related to investment, operational, maintenance costs, average number of catches/trips, average number of fishing trips and fish prices were obtained through structured interviews using questionnaires with respondents (ship owners, skippers, and crew fishermen). Sampling of respondents was done by purposive sampling. The results showed that financially (profit) and investment (Net B/C, IRR, BEP, and PP) the pole and line fishery business KM Mina Maritim 145 capacity 30 GT and KM Inka Mina 520 capacity 37 GT was feasible to be cultivated throughout the year. Based on business feasibility (financial and investment criteria), the huhate fishery business of the two ships has high sustainability. The pole and line fishery business in the research location has a high sustainability status, therefore it needs attention from the local government, so that the fishery business continues for the sake of increasing regional income and community welfare while still paying attention to the sustainability of the natural resources used.